The use of HEPES-buffer in the production of gallium-68 radiopharmaceuticals - time to reconsider strict pharmacopoeial limits? - Jannie le Roux; Janke Kleynhans; Sietske Rubow (SpringerOpen, 2021)
Abstract HEPES (4-(2-hydroxyethyl) piperazine-1-ethanesulfonic acid) is a buffer that is used in the radiolabelling of gallium-68 compounds. The beneficial effects of HEPES on molar activity in bioconjugates have been well described. Current strict regulations on the HEPES content in radiopharmaceuticals limit its use when intended for parenteral administration. This short communication summarizes data from the literature on the toxicity of HEPES in dogs after intravenous infusion and the subsequent use in humans. We also highlight the use of HEPES in an FDA labelled intravenous drug formulation. Regulatory institutions may consider this data to review current strict limits.